Developing an Integrated Methodology for Estimating Economic Efficiency of Production in Agricultural Enterprises Republic of Moldova - Timofti, Elena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
This paper presents an analysis to estimate the economic efficiency of agricultural products and global production in agricultural enterprises in Moldova. It was determined by using a system of partial indicators of economic efficiency dynamics from 2005-2012. Along with traditional indicators, a calculation methodology developed by a synthetic indicator for (full) efficiency was used, taking into account basic indicators of production and sales. The recommended methodology enables: trace-back to each farm unit for economic efficiency compared with border hierarchy of optimal studied (standard) levels of identification, with results by influence; determining reserves to increase economic efficiency etc. The following methods are based on economic statistics research: monographic method, method table, DEA (Data Envelopment Analysis). In the research the author used data from specialized forms of agricultural enterprises from the Statistical Yearbook (NBS).